Welcome to the Soviet Union : Magnolia air charter holidays, summer 1976 (Intourist Moscow Ltd, 1976)
Colour photographs of various places and ethnicities from the Soviet Union Poster advertising package holidays from Britain to the Soviet Union PO-1552